2016
DOI: 10.1038/mp.2016.213
|View full text |Cite
|
Sign up to set email alerts
|

Gestational vitamin D deficiency and autism-related traits: the Generation R Study

Abstract: There is intense interest in identifying modifiable risk factors associated with autism-spectrum disorders (ASD). Autism-related traits, which can be assessed in a continuous fashion, share risk factors with ASD, and thus can serve as informative phenotypes in population-based cohort studies. Based on the growing body of research linking gestational vitamin D deficiency with altered brain development, this common exposure is a candidate modifiable risk factor for ASD and autism-related traits. The association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 66 publications
4
117
3
1
Order By: Relevance
“…A recent study of postmortem neural tissue of children with ASD identified local disorganization across different cortical layers suggestive of aberrant prenatal neuronal migration [Stoner et al, ]. Environmental factors, such as maternal thyroid dysfunction or vitamin D deficiency may lead to autism‐like symptoms through restriction of prenatal brain growth [Korevaar et al, ; Román et al, ; Vinkhuyzen et al, ; Whitehouse et al, ]. Alternatively, autistic traits and prenatal HC growth may share a similar genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of postmortem neural tissue of children with ASD identified local disorganization across different cortical layers suggestive of aberrant prenatal neuronal migration [Stoner et al, ]. Environmental factors, such as maternal thyroid dysfunction or vitamin D deficiency may lead to autism‐like symptoms through restriction of prenatal brain growth [Korevaar et al, ; Román et al, ; Vinkhuyzen et al, ; Whitehouse et al, ]. Alternatively, autistic traits and prenatal HC growth may share a similar genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…Daraki et al investigated the association of maternal 25-hydroxyvitamin D [25(OH) D] levels with multiple neurodevelopmental and cognitive outcomes at 4 years of age in a prospective pregnancy cohort including 487 mother-child pairs [7]. Low gestational maternal vitamin D levels had been previously linked to autism-related neurodevelopmental outcomes in population-representative samples [8]. In the new study, a broad range of behavioural problems and externalizing symptoms, including hyperactivity, impulsivity, and also inattention, were significantly lower in children born to mothers within the high 25(OH) D tertile (> 50.7 nmol/l) as compared to offspring of women in the low 25(OH) D tertile (< 38.4 nmol/l), supporting a protective effect of high maternal vitamin D levels in early * Carmen Moreno cmoreno@hggm.es pregnancy on childhood behavioural outcomes, independent of cognitive factors.…”
mentioning
confidence: 99%
“…has been implicated with both psychotic and affective disorders [16][17][18][19][20][21][22] and since it acts as an epigenetic regulator during neurodevelopment, it has the potential to integrate intrinsic and environmental signals into the shaping of the maturing brain. Here, we demonstrate that 74 and autism spectrum disorder 75,76 ), and genome wide association of loci harboring the RXRG in bipolar disorder 77 and attention deficit hyperactivity disorder 77 , LXRA in autism spectrum disorder 78 , and NR4A2 in major depressive disorder 79 . Gene set and pathway analyses of GWAS data in major depressive disorder and bipolar disorder additionally reveal enrichment of genes implicated with thyroid hormone and retinoic acid signaling 60 as well as genes containing RAR/RXR consensus sequences 79 .…”
Section: Discussionmentioning
confidence: 60%